Some Difference Inequalities for Iterated Sums with Applications - Wu-Sheng Wang; Shanhe Wu (Abstract and Applied Analysis)
The main objective of this paper is to establish two new nonlinear sum-difference inequalities with multiple iterated sums. Under several practical assumptions, the inequalities are solved through rigorous analysis, and explicit bounds for the unknown functions are given clearly. These new inequalities can be used as handy tools in the study of the estimation of solutions of difference equations.